Film Pendek Zero Waste Lifestyle Menggunakan Animasi 3D - Syam, Supriadi (JTRISTE, 2023)
Waste is our common problem, there are many problems that arise due to humans' lack of discipline in managing waste so that it is scattered everywhere, polluting the land and sea and becoming one of the causes of climate change. This research focuses on the implementation of multimedia technology in the form of 3D animation to illustrate the impact of bad human behavior and habits that are less environmentally friendly and introduce a Zero waste lifestyle. Zero waste lifestyle is a lifestyle concept that invites us to Use disposable products wisely to reduce the amount and impact of waste. This short film is made in 3D animation in order to present an attractive appearance so that it is easy to attract the attention of the audience. The use of animation can be shown with particle simulation so that the objects in it seem more real. The result of this research is a short film which is an educational tool to increase awareness to reduce the use of single-use products and better protect the environment. Based on the respondents' answers, it was found that 61.8% of respondents agreed to the storyline and messages conveyed and the film's animation.